TechTip: Lucid, a tool for identifying pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
To identify an insect, an entomologist will first narrow down the range of possibilities by examining the creature´s appearance.